The Labour-Management Relationship and Organization Outcomes : Some Initial Findings - Wagar, Terry (Relations industrielles / Industrial Relations, 1997)
Based on responses from 752 unionized organizations in Canada, this study examines the association between the quality of labour-management relations and a number of organization outcomes. The average relationship between an employer and its major bargaining unit was moderately cooperative, with 28% of respondents reporting adversarial relations and 5% indicating a highly cooperative relationship. Results from ordered probit estimation indicated that more favourable organizational outcomes (as measured by management perceptions) were generally associated with a more coopérative relationship between union and management.